Crystalchair: arm chair / Nasrul Hakim Mohd Noor - Mohd Noor, Nasrul Hakim (College of Creative Arts, Universiti Teknologi MARA Kedah Branch, 2022)
This Armchair is based on crystal; Crystals are classified into general categories, such as insulators, metals, semiconductors, and molecular and solids. A single crystal of an insulator is usually transparent and resembles a piece of glass. Metals are shiny unless they have rusted. Semiconductors are sometimes shiny and sometimes transparent but are never rusty. Many crystals can be classified as a single type of solid, while others have intermediate behaviour. Molecular solids are usually crystals formed from molecules or polymers. They can be insulating, semiconducting, or metallic, depending on the type of molecules in the crystal. New molecules are continuously being synthesized, and many are made into crystals. The number of different crystals is enormous. CRYSTALCHAIR is these chairs feature crystal features in each board shape and the entire rod metal shape that has been connected using the welding method, this armchair is eco-friendly and ergonomic shape because every corner board shape or metal has been fillet surface for avoiding injury. For the colour the armchair is blue, and this armchair can be used for all ages. Humans observed and tried to learn about natural forms and structures. Designers have also observed how life proceeded in nature and began to develop the furniture by observing or imitating the natural structures. Nature gave them plenty of opportunities with its admirable mechanisms, designs and potential to enrich various aspects of life. As a result of the increase of our accumulation of knowledge and the development of technological opportunities, this potential reveals itself a bit more in every single day to become furniture designer, student needs to clearly define the problems and proposed possible solution related to furniture design. In this lesson, students are encouraged to explore and developed furniture that can fit their ever-changing needs. Apart from that, they can create new furniture designs that can give awareness of nature and inspire others.